The Effect of Cooperative Learning Jigsaw Model on Students’ Vocabulary Mastery of the Fourth Grade at Elementary School Bakungan - Eva Amalia Fitriani; Sutami Dwi Lestari; Wahyudi Arifiyanto; Viona Asti Audina (LUNAR, 2026)
This research was about the effect of the Cooperative Learning Jigsaw Model on students’ vocabulary mastery of the fourth grade at Elementary School Bakungan. The objective of this research was to find out whether there was an effect of the Cooperative Learning Jigsaw Model on the students’ vocabulary mastery of the fourth graders. The method used in this research was an experimental quantitative method with a one-group pretest–posttest research design. The respondents of this research were 27 fourth-grade students. This research used the Jigsaw Model test to collect the data. The result of the t-test was 2.39 and the t-table value was 1.70 at the 5% significance level with a degree of freedom of 26. It showed that the t-test value was higher than the t-table value. This data analysis was also strengthened by the average scores of the students. The average score of the respondents’ post-test results was 75.37, which was higher than 52.04 in the pre-test of the experimental group. Based on the results of the data analysis and discussion, it could be concluded that there was an effect of the Cooperative Learning Jigsaw Model on the students’ vocabulary mastery of the fourth grade at SDN 1 Bakungan.